Visualization of Protein Interactions in Living Cells Using Bimolecular Luminescence Complementation (BiLC). (13th February 2018) - Verhoef, Lisette G.G.C.; Wade, Mark
Abstract: The number of intracellular protein‐protein interactions (PPIs) far exceeds the total number of proteins encoded by the genome. Dynamic cellular PPI networks respond to external stimuli and endogenous metabolism in order to maintain homeostasis. Many PPIs are directly involved in disease pathogenesis and/or resistance to therapeutics; they therefore represent potential drug targets. A technology generally termed 'bimolecular complementation' relies on the physical splitting of a molecular reporter (such as a fluorescent or luminescent protein) and fusion of the resulting two fragments to a pair of interacting proteins. When these proteins interact, they effectively reconstitute the activity of the molecular reporter (typically leading to increased fluorescence or luminescence). This unit describes the selection and development of bimolecular luminescence complementation (BiLC) assays for reporting intracellular PPIs, and provides examples in which BiLC was used to identify small molecules that can modulate PPIs. © 2017 by John Wiley & Sons, Inc.